Experimental investigation of a two-phase closed thermosyphon solar water heater - Esen, M; Esen, H (Pergamon-Elsevier Science Ltd, 2005)
In this study, experiments were performed to find out how the thermal performance of a two-phase thermosyphon solar collector was affected by using different refrigerants. Three identical small-scale solar water heating systems, using refrigerants R-134a, R407C, and R410A, were constructed and tested side-by-side under various environmental and load conditions. The performance of the system under clear-sky conditions has been investigated with and without water load. Detailed temperature distributions and cumulative collection efficiencies were determined and presented. The experimental results were compared to the results found in the literature and they showed good agreement. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: phase-change; heat-pipe solar collector; refrigerant-charged solar collector; solar water heating